EFFICACY AND SAFETY OF LOCAL INTRACORONARY ADRENALINE IN THE TREATMENT OF NO RE-FLOW PHENOMENON - SAOOD , Y; KAZMI , SIA; SALMAN , A; KHAN , MI; ZAFAR , R (Biological and Clinical Sciences Research Journal, 2023)
No flow is defined as the lack of myocardial perfusion despite opening up the epicardial coronary vessels in percutaneous coronary intervention (PCI). The study aims to find the efficacy and safety of local intracoronary adrenaline in treating the no-reflow phenomenon. This prospective observational study was conducted at the Peshawar Institute of Cardiology from January 2021 to January 2022. Data was collected from 86 patients. Data was collected through clinical assessments, angiographic evaluations, and patient records. Relevant baseline characteristics, procedural details, and outcomes were systematically documented for each participant. The average age of the participants was 62 years, with a gender distribution of 60% male and 40% female. Among the 86 patients, 42% exhibited an angiographically confirmed no-reflow phenomenon during PCI. No-reflow severity varied, with 18% experiencing mild, 15% moderate, and 9% severe no-reflow. Local intracoronary adrenaline was administered as part of the treatment strategy for the no-reflow phenomenon in the eligible patients. The standardized dose of adrenaline used was 100 μg, administered via the intracoronary route during the PCI procedure. It is concluded that local intracoronary adrenaline administration appears to be a potentially effective and safe strategy for managing the no-reflow phenomenon during PCI procedures.